2013
DOI: 10.2134/jeq2012.0504
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics Modeling of Nitrogen Removal in a Stormwater Infiltration Basin with Biosorption‐Activated Media

Abstract: Stormwater infiltration basins, one of the typical stormwater best management practices, are commonly constructed for surface water pollution control, flood mitigation, and groundwater restoration in rural or residential areas. These basins have soils with better infiltration capacity than the native soil; however, the ever-increasing contribution of nutrients to groundwater from stormwater due to urban expansion makes existing infiltration basins unable to meet groundwater quality criteria related to environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies tried to address the ecological significance of DON in various environments such as marine ,, and freshwater systems. ,, These studies revealed that DON is a structurally complex mixture of different kinds of organic molecules that are highly variable in chemical structure and composition and thus in bioavailability and ecological functioning. The inherent complexity of DON is a major barrier for understanding how different best management practices (BMPs) can change, modify, and remove DON through innovative stormwater treatment processes. One of the promising media types, biosorption activated media (BAM), has been used in various BMPs in varying landscapes for effective nitrogen removal through biological nitrification and denitrification. ,, However, the interaction between BAM and DON remains unclear, especially for the cotreatment of stormwater and groundwater in linear ditch (bioswale) facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies tried to address the ecological significance of DON in various environments such as marine ,, and freshwater systems. ,, These studies revealed that DON is a structurally complex mixture of different kinds of organic molecules that are highly variable in chemical structure and composition and thus in bioavailability and ecological functioning. The inherent complexity of DON is a major barrier for understanding how different best management practices (BMPs) can change, modify, and remove DON through innovative stormwater treatment processes. One of the promising media types, biosorption activated media (BAM), has been used in various BMPs in varying landscapes for effective nitrogen removal through biological nitrification and denitrification. ,, However, the interaction between BAM and DON remains unclear, especially for the cotreatment of stormwater and groundwater in linear ditch (bioswale) facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the toxicity of ammonia is fatal to many aquatic creatures even in a low concentration [5]. Different kinds of green sorption media with the inclusion of recycled materials have been adopted in various best management practices for nutrient removal from stormwater runoff [6][7][8][9][10][11][12][13][14][15][16][17]. Although removal efficiency is fair, it is difficult to achieve a desirable level of removal recovery.…”
Section: Introductionmentioning
confidence: 99%